Can we alter behaviours without "culture change"?. Issue 5 (8th April 2014) - Coulson-Thomas, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of the article is to share certain findings of a five-year investigation. Design/methodology/approach – It draws upon under-pinning research reports and analysis of early adoptions of what the evidence suggests is the most affordable route to high performance organisations. Findings – Many corporate culture change programmes are unnecessary if their purpose is to quickly change behaviours and can be problematic in organisations that need to embrace a diversity of cultures and a variety of approaches and behaviours across different functions and business units. Practical implications – Performance support can be a cost-effective way of changing behaviour, ensuring people remain current and competitive and delivering multiple objectives without requiring a change of culture or structure. Originality/value – The article suggests that a "new leadership" and shift of emphasis is required.